Tinjauan Yuridis terhadap Pelaku Perkara Tindak Pidana Persetubuhan: Studi Putusan Nomor 324/Pid.Sus/2024/PN TBH - M. Ari Pernando; Siti Rahmah; KMS. Novyar Satriawan Fikri (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study analyzes the juridical review of the defendant in the criminal offense of sexual intercourse with a child based on Decision Number 324/Pid.Sus/2024/PN Tbh and examines the judges’ legal considerations in rendering the verdict. The research uses a normative legal method with statutory and case approaches. Primary, secondary, and tertiary legal materials are analyzed qualitatively using a descriptive method. The findings show that the law enforcement process was conducted in accordance with the Indonesian Code of Criminal Procedure, the Indonesian Criminal Code, and Law Number 17 of 2016 concerning Child Protection. The criminal offense was proven through valid evidence, including witness testimonies, the victim’s testimony, the visum et repertum, and the defendant’s statement. The judges’ decision reflected the principles of legality, legal certainty, and justice. However, the continued occurrence of child sexual intercourse cases indicates that repressive law enforcement alone is insufficient, highlighting the need to strengthen criminal law policies and child protection measures.